A time and frequency synchronization scheme for multiuser OFDM. - Van de Beek, J.-J.
We present a multiuser synchronization scheme for tracking the mobile's uplink time and frequency offsets. It uses the redundancy introduced by the cyclic prefix and does not need additional pilots. We show performance results of an orthogonal frequency division multiplexing (OFDM)-based radio interface based on the universal mobile telecommunication system (UMTS) parameters. For a UMTS-typical mobile channel environment, the performance of a coherent system employing the scheme is virtually indistinguishable from the performance of a perfectly synchronized system. In a differentially modulated system, synchronization errors decrease the system performance by about 0.7 dB compared to a perfectly synchronized system
Keywords: UMTS; Coherent system; Cyclic prefix; Differentially modulated system; Frequency offset estimation; Frequency offset tracking; Frequency synchronization; Hybrid TDMA/FDMA scheme; Mobile channel environment; Mobile uplink; Multiuser OFDM; Orthogonal frequency division multiplexing; Performance results; Radio interface; Symbol error rate; Synchronization errors; System performance; Time offset tracking; Time synchronization; Universal mobile telecommunication system